2011
DOI: 10.1152/ajpheart.00985.2010
|View full text |Cite
|
Sign up to set email alerts
|

Repeated increases in blood flow, independent of exercise, enhance conduit artery vasodilator function in humans

Abstract: This study aimed to determine the importance of repeated increases in blood flow to conduit artery adaptation, using an exercise-independent repeated episodic stimulus. Recent studies suggest that exercise training improves vasodilator function of conduit arteries via shear stress-mediated mechanisms. However, exercise is a complex stimulus that may induce shear-independent adaptations. Nine healthy men immersed their forearms in water at 42°C for three 30-min sessions/wk across 8 wk. During each session, a pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 40 publications
7
99
1
10
Order By: Relevance
“…When looking at functional as opposed to structural outcome measures, a large number of previous studies in animals (Langille et al 1989;Langille and O'Donnell 1986) and humans (Tinken et al 2010;Rowley et al 2011) have identified shear stress as the key stimulus for localised adaptation in conduit arteries. For example, recent studies in humans found that that adaptation in BA function as measured by flow mediated dilation in response to 8-weeks exercise training (Birk et al 2012;Tinken et al 2010) or heat exposure (Naylor et al 2011) are abolished in the contra-lateral arm when the increases in shear rate are mitigated by subdiastolic cuff inflation. Interestingly, when a similar design was used to examine the importance of the shear rate stimulus for adaptation in wall thickness, the abolished shear stimulus did not prevent the decreases in BA WT across 8-weeks of handgrip training (Thijssen et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…When looking at functional as opposed to structural outcome measures, a large number of previous studies in animals (Langille et al 1989;Langille and O'Donnell 1986) and humans (Tinken et al 2010;Rowley et al 2011) have identified shear stress as the key stimulus for localised adaptation in conduit arteries. For example, recent studies in humans found that that adaptation in BA function as measured by flow mediated dilation in response to 8-weeks exercise training (Birk et al 2012;Tinken et al 2010) or heat exposure (Naylor et al 2011) are abolished in the contra-lateral arm when the increases in shear rate are mitigated by subdiastolic cuff inflation. Interestingly, when a similar design was used to examine the importance of the shear rate stimulus for adaptation in wall thickness, the abolished shear stimulus did not prevent the decreases in BA WT across 8-weeks of handgrip training (Thijssen et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the impact of repeated exposure to elevations in antegrade shear stress via training, heating, or in vitro manipulation of antegrade shear 7, 13, 14, 15, 16, 17. These studies consistently report a dose‐dependent increase in arterial caliber and improvement in endothelial function, possibly through upregulation of endothelial nitric oxide synthase 1, 18.…”
Section: Introductionmentioning
confidence: 99%
“…This is inferred from recent studies that have demonstrated that heat stress may result in similar muscle adaptations to that observed following endurance exercise (Harris et al, 2003;Hooper, 1999;Liu & Brooks, 2012;Naylor et al, 2011;Yamaguchi et al, 2010). For instance, mild heat stress (39-40°C) has been shown to increase PGC-1α activity and induce PGC-1α mRNA and protein expression in a variety of muscle cell lines (Liu & Brooks, 2012;Yamaguchi et al, 2010), in addition to an increase in the mRNA content of key mitochondrial transcription factors (NRF1, NRF2 and Tfam), complex-IV subunits (COX2 and COX4) as well as glucose transporter 4 (GLUT4) mRNA (Liu & Brooks, 2012).…”
Section: Role Of Temperature In Pgc-1α Mediated Adaptations Passive Hmentioning
confidence: 81%
“…The production of metabolic heat during exercise appears to have a role in muscle oxidative phenotype transformations (Harris et al, 2003;Hooper, 1999;Liu & Brooks, 2012;Naylor et al, 2011;Yamaguchi et al, 2010). This is inferred from recent studies that have demonstrated that heat stress may result in similar muscle adaptations to that observed following endurance exercise (Harris et al, 2003;Hooper, 1999;Liu & Brooks, 2012;Naylor et al, 2011;Yamaguchi et al, 2010).…”
Section: Role Of Temperature In Pgc-1α Mediated Adaptations Passive Hmentioning
confidence: 93%
See 1 more Smart Citation